The indicator of underlying inflation: Basic idea and use - Mikko Spolander (Bank of Finland, 1994)
February 1993 the Bank of Finland announced an inflation target the aim of which is to stabilize the inflation rate, as measured by the indicator of underlying inflation (IUI), permanently at the two per cent level by 1995.The IUI is the consumer price index (CPI) from which the effects of indirect taxes, subsidies and housing-related capital costs, i.e. house prices and mortgage interest payments, have been removed. Removing the effects of housing-related capital costs from the overall CPI simply means that a new consumption basket is constructed without them.The exclusion of the effects of indirect taxes and subsidies is more discretionary.The procedure is the same as in the case of the net price index (NPI).The indicator of underlying inflation is actually a type of net price index.It acts like the NPI and has the same weaknesses as the NPI. In practice the removal of the effects of changes in the rates of indirect taxes and subsidies is not simple or transparent. The size of the overall effect can be estimated reliably enough on the basis of the effect on the central government revenue for the same year.But, unfortunately, nobody knows how long it will take for this effect to be passed through into consumer prices.All the errors in estimating the pass-through lags are also reflected in the IUI.The IUI remains sensitive to these estimation errors and, hence, some of the monthly changes in the IUI will undoubtedly be difficult to interpret. The price effects of Finland's EU membership serve as a good illustration of the effects of a structural change on the behaviour of the IUI.
URN:NBN:fi:bof-20140807368
Keywords: 330